International Trade Law as an Instrument of Global Economic Integration: A Normative Study of the Role of the World Trade Organization - Indra Setiawan; Zul Karnen (Eduvest - Journal of Universal Studies, 2026)
Economic globalization has led to the birth of an integrated international trading system through multilateral legal regimes. International trade law no longer merely regulates cross-border transactions, but has developed into an instrument of global economic integration that shapes the national policy structure of member states. The World Trade Organization (WTO) plays a central role as an institution that institutionalizes the principles of liberalization, non-discrimination, and certainty of trade law through various multilateral agreements. This research aims to analyze the position of international trade law as an instrument of global economic integration and examine the normative role of the WTO in shaping world trade governance. The method used is normative legal research with legislative, conceptual, and comparative approaches. The results of the study show that the WTO has succeeded in creating harmonization of global trade standards through the principles of Most Favoured Nation, National Treatment, and a binding dispute resolution mechanism. However, such integration still leaves the problem of structural inequality between developed and developing countries, the weak effectiveness of Special and Differential Treatment, and limited national policy space. Therefore, WTO governance reform and strengthening the domestic capacity of developing countries are needed so that global economic integration takes place in a fair and sustainable manner.